Fakta-fakta Ilmiah dalam Peristiwa Arkeologi dan Sejarah (Telaah Kemukjizatan Al-Qur'an) : Scientific Facts in Archaeological and Historical Events (an Examination of The Miracles of The Qur'an) - Gampang Dadiyono; Halimah Basri; Ahmad Mujahid (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
This research aims to reveal scientific facts that support the miraculousness of the Qur'ān in this modern era. With the development of technology and science, humans have greater opportunities to prove the accuracy of the Qur'an from various scientific perspectives. The research method used is library research by reviewing books related to the research. The results of this study indicate that the miracle of the Qur'an (i'jazul Qur'an) is proven not only through language and legal aspects, but also through scientific and historical facts revealed in this holy book. Archaeological discoveries such as the existence of the people of 'Ad and Tsamud, the body of Pharaoh, as well as the story of Prophet Ibrahim and Ashabul Kahfi, provide concrete evidence that reinforces the truth of the Qur'an from a historical and scientific point of view. This research emphasizes that the Qur'ān is not only relevant as a spiritual guide, but is also able to answer the challenges of modern rationality, confirming its position as a miracle that surpasses human capabilities and is relevant throughout the ages.